El Arte Infantil en el Desarrollo de la Inteligencia Emocional de los niños y niñas de 2 a 3 años del “Centro Infantil Universitario” de la Parroquia Guanujo, Cantón Guaranda, Provincia de Bolívar, año lectivo 2015 – 2016. - Ayala Gavilanes, Diana Catalina (2016)
The art of development of emotional intelligence is a research work carried out at Centro Infantil Universitario in the city of Guaranda with children of 2 and 3 years of age in order to improve self-teem social skills, and management of emotions. So, it was decided to study the causes which the art was not applied in order to reach an optimum emotional development. Chapter I in includes the theoretical framework based on information taken from the Universida Nacional de Chimborazo library, Centro Infantil Universitario, and internet. Scientific foundation was based on the Daniel Goleman, the management of emotions facing social and personal problems and control of impulses which affected the others. Chapter II contains the methodology with a descriptive applied research and deductive – inductive method. Interview to teachers and observation to children in the Centro Infantil Universitario were used in data collection. Chapter III has alternative guidelines and the guide of artistic activities as a didactics tool in the order to identify emotions of the others by controlling and managing them. Chapter IV includes presentation and discussion of results by the means of the application the observation guide before and after the application of the guide of artic activities as a didactic tool to develop emotional intelligence and prove the hypothesis two which said that childhood art and emotional intelligence were related each other. Chapter V contains conclusions and recommendations, elaboration of the guide of artistic activities as a didactic tool to develop emotional intelligence “Art an emotional flight”. Teachers were recommended to apply artistic activities in children if Initial I, and replicate as many times as necessary in other to improve emotional status based on humane behavior.